2023
DOI: 10.37745/bjmas.2022.0302
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Health Risks of Inorganic Toxicants in Gallus Gallus Domesticus (Broilers) in Uyo, Nigeria

Helen Solomon Etuk,
Godwin Asukwo Ebong,
Idongesit Bassey Anweting
et al.

Abstract: Poultry-related foods are consumed as good and cheap sources of protein globally. This research investigated the levels of Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn in poultry feeds, water samples, and broilers obtained from poultry farms randomly sampled within Uyo Metropolis. These poultry-related products were obtained, treated, and analysed spectrophotometrically using standard analytical techniques. Results showed that, the concentrations of all the metals in poultry feeds and broiler meat were within their reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 104 publications
1
4
0
Order By: Relevance
“…Consequently, prolonged exposure to the studied samples with EDI values higher than their recommended oral limit may result in severe health hazards. The EDI results also revealed that, the children population was more susceptible to the health risks related to the persistent exposure to these toxic metals through the studied samples as reported by Rakib et al [75].…”
Section: Estimated Daily Intake Rate Of Toxic Metalssupporting
confidence: 74%
See 1 more Smart Citation
“…Consequently, prolonged exposure to the studied samples with EDI values higher than their recommended oral limit may result in severe health hazards. The EDI results also revealed that, the children population was more susceptible to the health risks related to the persistent exposure to these toxic metals through the studied samples as reported by Rakib et al [75].…”
Section: Estimated Daily Intake Rate Of Toxic Metalssupporting
confidence: 74%
“…These metals include arsenic, cadmium, chromium, nickel lead, and mercury [11,12]. These metal toxicants are capable of causing both the carcinogenic and noncarcinogenic human health problems [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This can be the negative impact of anthropogenic activities on the quality of the Qua Iboe River Estuary, [80]. The identification of the actual sources of trace metals in sediments from the studied aquatic ecosystem was done by the use of principal component analysis (PCA), [81,82]. During the dry season, the PCA revealed two major sources of trace metals in the studied sediments with a total variance of 87.38%.…”
Section: Seasonal Variations Of Trace Metals In Sediments From the St...mentioning
confidence: 99%
“…Hierarchical cluster analysis of trace metals in the studied sediments for both seasons resulted in a similar cluster as illustrated in Figure above Hierarchical cluster analysis (HCA) of trace metals in sediments from rivers investigated for both the dry and wet seasons resulted in a similar pattern as shown in Figure 5. The HCA is tool that reveals parameters with similar source and properties in a media, [26,81]. Results of HCA in Figure 5 indicate three (3) major clusters namely: Cluster 1 links Mn, Cu, Pb, and Cd together.…”
Section: Figurementioning
confidence: 99%
“…Metals have the potential to bioaccumulate in living cells through ingestion [3][4][5]. The accumulated metals can cause adverse health problems ranging from cancerous to non-cancerous [6][7][8][9]. The generation of electric power in Nigeria in 1896 has resulted in both positive and negative implications associated with the generation, transmission, and distribution [10,11].…”
Section: Introductionmentioning
confidence: 99%